Uji Standar Mutu Sabun padat transparan minyak atsiri sereh wangi ( Cymbopogon nardus L ) (Politeknik Medica Farma Husada Mataram, 2021)
Transparent solid soap is a bar-shaped soap with a transparent appearance, resulting in a softer foam on the skin and appearance is more shiny than other types of soap. Soap quality standards are needed to determine the quality of soap. This research aims to find out the quality standards of soap formula whether it meets SNI standards. Quality standard tests from the study were taken from transparent soap formulations using the active substances of fragrant lemongrass essential oil on a VCO basis made by the watering method (Fx). Evaluation of the quality standards of transparent solid soaps of fragrant lemongrass essential oil (Cymbopogon nardus L) is a free alkaline test, pH test, water content test using a comparison soap containing essential oils circulating in the market (Fy). Quality standard test results on the Fx and Fy formulas are on the verge of pH 9-11 meeting SNI standards. While the results of fx and Fy formula testing on water content testing > 15% and alkali free > 0.1% so it does not meet SNI standards. So the transparent solid soap formula of fragrant lemongrass essential oil (Cymbopogon nardus L) has not met the required SNI standards.